Producción de biogás a partir de la codigestión de biomasa residual en un sistema de digestión anaerobia con agitación a escala laboratorio (2018)
This project aims to contribute to the use of waste and the generation of new energy sources, through the biochemical transformation of residual biomass through the process of anaerobic digestion, contributing to research in the area and within the Energy research group. Alternatives of the Fundación Universidad de América . To develop the project as the first phase, the wet biomass of interest was selected and characterized: bovine manure and pruning residue, taking into account availability, biochemical composition and collection form. For the preparation of the biomass, reduction of the particle size to the pruning residue was made; finally, the pH was evaluated being 7.3 for bovine manure and 6.24 for pruning residue. In the same way, a humidity percentage higher than 60% was determined for the two types of biomass.